A COMPREHENSIVE APPROACH TO FORMING ENTERPRISE RISK MANAGEMENT SYSTEMS - PROKOPCHUK, Liliya; BURYKIN, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In the modern era of digital business transformation, enterprises face risks of various origins caused by globalization, market instability, and rapid technological advancements. Effective risk management has become a crucial factor in ensuring the stability and competitiveness of enterprises. Implementing a comprehensive risk management approach allows for accurate analysis and threat control, contributing to loss minimization and sustainable business development. The increasing number and variability of risks create significant challenges in developing an effective risk management system for enterprises. This necessitates new approaches that consider technical, financial, organizational, and legal aspects. The implementation of such an approach is essential for ensuring business sustainability and minimizing the impact of crisis situations. The aim of this study is to develop a comprehensive approach to forming an enterprise risk management system in the modern economic environment. Risk management is a multifactorial process that includes several key stages: identification, assessment, development of response strategies, and monitoring. Identification involves determining potential threats, while assessment analyzes the probability of their occurrence and their impact on business. Based on this data, strategies are developed to minimize or transfer risks, including insurance, the use of derivatives, or the implementation of internal control measures. Digital technologies enhance analysis accuracy and response speed, analytical platforms enable scenario modeling, and IoT solutions provide real-time monitoring. However, implementing these technologies requires overcoming barriers related to high financial costs and cybersecurity threats. A strategic approach to enterprise risk management considers the long-term perspective and integrates all management aspects into a unified system. This approach not only enables enterprises to adapt to changing business environments but also creates new opportunities for the development of domestic enterprises.. In the modern context of dynamic changes and digital business transformation, risk management has become an integral component of enterprise strategy. A comprehensive approach allows for the consideration of various threats and creates conditions for sustainable business development. The inclusion of financial, technical, organizational, legal, and market aspects makes this approach an effective tool for identifying, assessing, and minimizing risks. The key stages of risk management include identification, assessment, development of response strategies, and monitoring. The importance of each stage lies in ensuring a timely response to environmental changes. Digital technologies, such as analytical platforms and IoT, significantly enhance management efficiency by automating processes and reducing the impact of the human factor. Despite the advantages of digital solutions, there are challenges such as significant financial costs, insufficient digital literacy of staff, and cybersecurity threats. Overcoming these barriers requires investment in training, the development of security policies, and the implementation of modern technologies. A strategic approach to risk management integrates various aspects of operations, contributing to the formation of long-term solutions. As a result, enterprises can mitigate the impact of crisis situations and maintain competitiveness. Thus, risk management is an important tool for ensuring business stability and development. Future research should focus on adapting management models to the specifics of different industries and assessing the effectiveness of digital technologies in the long-term perspective.